2006
DOI: 10.1029/2005jb003854
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission and velocities associated with the formation of compaction bands in sandstone

Abstract: [1] A series of laboratory experiments has been conducted in which three-dimensional (3-D) locations of acoustic emissions (AE) were recorded and used to analyze the development of compaction bands in Bleurswiller sandstone, which has a porosity of 25%. Results were obtained for saturated samples deformed under triaxial compression at three different confining pressures (60, 80, and 100 MPa), a pore pressure of 10 MPa, and room temperature. We recorded acoustic emissions, compressional and shear wave velociti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
181
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(194 citation statements)
references
References 41 publications
11
181
0
Order By: Relevance
“…The damage almost linearly increases with increasing axial strain: Microcracks accumulate as shear bands are formed, but the sample keeps its integrity. To our knowledge, our data set is the first to show such a linear relationship between crack density and deformation; typically, brittle rocks accumulate microcracks nonlinearly prior to localization [Schubnel et al, 2003;Fortin et al, 2006].…”
Section: Micromechanics Of Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The damage almost linearly increases with increasing axial strain: Microcracks accumulate as shear bands are formed, but the sample keeps its integrity. To our knowledge, our data set is the first to show such a linear relationship between crack density and deformation; typically, brittle rocks accumulate microcracks nonlinearly prior to localization [Schubnel et al, 2003;Fortin et al, 2006].…”
Section: Micromechanics Of Deformationmentioning
confidence: 99%
“…Indeed, from a material science point of view, deformation is always localized at some particular length and timescale. AE signals have been used to characterize damage during rock deformation [e.g., Scholz, 1968;Mogi, 1968;Lockner et al, 1992] even in the ductile regime and in the absence of stick-slip [e.g., Baud et al, 2004;Fortin et al, 2006]. Thus, the record of AE during deformation cannot be systematically understood as the signature of a seismic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Olsson et al [5,6], Wong et al [7], Haimson et al [8][9][10][11], Baud et al [2] and Fôrtin et al [12] observed three different pat-terns of compaction bands in laboratory experiments [3]. Olsson and Holcomb [5,6] observed wide compaction bands in Castlegate sandstone, which grew in thickness with increasing axial load until the entire specimen was covered.…”
Section: Introductionmentioning
confidence: 99%
“…The bands spread across the specimen with increasing applied load, and were interlayered with less deformed materials. Fôrtin et al [12], Stanchits et al [15] and Charalampidou et al [16] conducted experiments with notched specimens, and observed compaction bands under lower stress levels. The third pattern of compaction bands was observed in specimens with a hole which created a heterogeneous stress field.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the conditions leading to the formation of compaction bands, which can produce destructive compartmentalization of reservoirs, one has to better understand how the occurrence of localized zones of compaction is related to the stress state and the constitutive properties of the rock. Development of this phenomenon has been investigated in the laboratory, primarily in sandstones with porosities ranging from 13% to 28% (DiGiovanni et al 2000;Klein et al 2001;Fortin et al 2006). The data show that localized failure in compactant rock is commonly associated with stress states in the transitional regime from brittle faulting to cataclastic flow , with the mode of localization associated with a broad spectrum of complexity Ngwenya et al 2003).…”
Section: Geomechanical Effects In Produced Reservoirsmentioning
confidence: 99%